2012
DOI: 10.1039/c1cs15089h
|View full text |Cite
|
Sign up to set email alerts
|

Update on selective oxidation using gold

Abstract: This critical review aims to update the recent development in the selective oxidation of organic compounds by gold catalysis, highlighting the progress in the last three years. Following the impressive developments in the last decades, several protocols for catalytic oxidation are today available, which are based on the extraordinary properties of gold in terms of catalytic activity, selectivity, reusability and resistance to poisons. Beside many other applications, gold can be recommended for green processes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
218
0
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 352 publications
(227 citation statements)
references
References 168 publications
(217 reference statements)
4
218
0
5
Order By: Relevance
“…1b, 2d), in agreement with previous work. [30] This structure is consistent with the length of (2+n)a of features along the [1][2][3][4][5][6][7][8][9][10] direction, as determined by STM. Within this structure model, features with n>2 darker gold atoms contain (n-2) atoms that are perturbed by two oxygen atoms.…”
Section: Stm Contrast On Oxygen On Au(110) and Its Origin Oxygen Atosupporting
confidence: 85%
See 2 more Smart Citations
“…1b, 2d), in agreement with previous work. [30] This structure is consistent with the length of (2+n)a of features along the [1][2][3][4][5][6][7][8][9][10] direction, as determined by STM. Within this structure model, features with n>2 darker gold atoms contain (n-2) atoms that are perturbed by two oxygen atoms.…”
Section: Stm Contrast On Oxygen On Au(110) and Its Origin Oxygen Atosupporting
confidence: 85%
“…[1] Prof. Madix, who is being honored by this special issue, was a pioneer in the application of scanning tunneling microscopy (STM) to the investigation of chemical reactions on surfaces, including coinage metals. [2] Because gold is an efficient and selective catalyst for oxidation processes [3][4][5][6][7][8][9] there is considerable interest in imaging reactant species, including adsorbed oxygen (O ads ), on its surfaces. Model studies on single crystal surfaces [10][11][12][13] provide a mechanistic understanding of how oxidative processes are promoted on Au, [14] with the final goal of predicting new reactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the pioneering works of Hutchings [1] and Haruta et al [2], the high activity of gold catalysts has demonstrated that gold can be the catalyst of choice for an important number of chemical reactions such as selective oxidations and hydrogenations of organic substrates [2][3][4][5][6], water-gas shift reaction [7][8][9], acetylene hydrochlorination [10,11], direct synthesis of hydrogen peroxide [12], reduction of NO to N 2 [13,14] and the addition of nucleophiles to acetylenes [15], among others [16,17]. Although gold has been sometimes alloyed with other metals such as Pd, Cu and Ag, in most cases, gold alone exhibits high and exceptional catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…From these studies, it was identified that when Au is present as very small particles, with a mean diameter below 10 nm, it becomes surprisingly catalytically active, especially at low temperatures. After these important discoveries, many research groups in academia and industry have focused their research upon exploring the catalytic performance of Au catalysts for a wide range of oxidation and hydrogenation reactions [5,6]. New discoveries have been reported since that period, and novel, designed supported gold nanoparticles have shown to be extremely effective catalysts for the oxidation of CO [7][8][9][10][11], the selective oxidation of alcohols and polyols [12,13], the epoxidation of olefins [14,15], the hydrochlorination of ethyne [16], the selective hydrogenation of unsaturated carbonyl and nitro groups [17], and the direct synthesis of hydrogen peroxide from molecular hydrogen and oxygen [18].…”
Section: Introductionmentioning
confidence: 99%